Pathogenic fungi infecting of soybean (Glycine max (L.) Merrill) roots and stem base - Elżbieta Patkowska (Acta Agrobotanica, 2013)
The studies were conducted in the years 1996 - 1998 on an experimental plot of the University of Agriculture in Lublin localised in Czesławice near Nałęczów. The subject of the studies was soybean. Polan cultivar, and their purpose was to determine the species composition of fungi infecting the roots and stem base of this plant in different stages of its growth. The studies showed that on an area of 1 m2, 61-70 soybean seedlings and 60-69 plants at anthesis grew. The proporlion of infected seedlings ranged from 14,3% to 18%, while at anthesis only a small increase of the number of infected plants was observed. In the case of seedlings, the following fungi turned out to be most harmful: P.irresulare, F.solani, R.solani and F.oxysporum f. sp. glycines. On the other hand, F.oxysporum f. sp. glycines had the greatest effect in infecting the roots and stem base ofplants at anthesis.